A ceramic filter for high-temperature alloy precision casting and its preparation method
By preparing ceramic powder and nanozirconia sol, combined with modified carbon fiber electrostatic flocking technology and the combined treatment of slurry and spray liquid, the problems of hole blocking, slag dropping, poor slurry hanging and low sintering strength of ceramic filters during high-temperature precision casting are solved, and the efficient preparation and performance improvement of ceramic filters are achieved.
Patent Information
- Application Number
- CN202411537966.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-10-31
AI Technical Summary
During the high-temperature precision casting process, existing ceramic filters have problems such as hole blocking, slag dropping, poor slurry hanging, low sintering strength and volume effects, which affect their application performance.
Multi-stage prepared ceramic powder and nanozirconia sol are used, combined with modified carbon fiber electrostatic flocking technology, to improve the solid content and surface hydrophilic performance of the precursor. Through the combination of soaking and spraying liquid, the slurry hanging effect is improved, and the crystal phase transformation during the sintering process is controlled to suppress the volume effect.
It effectively avoids hole blockage and slag loss problems in the high-temperature precision casting process of ceramic filters, improves the slurry hanging performance and sintering strength, suppresses the volume effect, and improves the overall performance of ceramic filters.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of ceramic filters, and in particular to a ceramic filter for high-temperature alloy precision casting and a preparation method thereof. Background Art
[0002] Ceramic filters have been widely used in high-temperature alloy precision casting technology as auxiliary materials for precision casting. Due to the high porosity of ceramic filters, three-dimensional network skeleton structure and through pores, and good high-temperature properties such as high-temperature thermal shock resistance and high-temperature bending strength, ceramic filters are used to filter and purify the molten metal during the precision casting of high-temperature alloys. Through mechanical blocking, rectifying slag, surface adsorption and other mechanisms, large inclusions and fine suspended inclusions in the molten metal can be removed efficiently, and the precipitation of some gases can be promoted. Ultimately, the inclusion content of high-temperature alloy precision castings can be greatly reduced, and the mechanical properties and service life of high-temperature alloy precision castings can be effectively improved. Based on this, it is very necessary to study and prepare high-performance ceramic filters, which are essential materials for the preparation of high-quality aircraft engine castings by high-temperature alloy precision casting.
[0003] The existing ceramic filters have high pore blocking rate and easy slag falling when used in high-temperature precision casting. At the same time, the ceramic filters also have the problem of low slurry volume in the preparation process, and need to be dried and then subjected to multiple slurry treatments, which not only leads to low production efficiency, but also causes the ceramic filter screen to have thin connection ribs and low skeleton strength after sintering, which ultimately leads to easy slag falling during the application of the ceramic filter, which is easy to contaminate the molten metal, and then leads to internal defects of precision castings (such as pores, sand holes, etc.).
[0004] Furthermore, the existing ceramic filters for high-temperature alloy precision casting cannot effectively suppress the volume effect caused by the m-phase-t-phase transformation during the preparation process, resulting in large sintering shrinkage, which easily causes deformation and cracking of the ceramic filters. In addition, the sintering strength of the ceramic filters needs to be further improved. Summary of the invention
[0005] In order to solve the technical problems existing in the prior art, the present invention provides a ceramic filter for high-temperature alloy precision casting and a preparation method thereof, which can effectively avoid the problems of hole clogging and slag falling of the ceramic filter during the high-temperature precision casting process; effectively improve the slurry hanging performance of the ceramic filter during the preparation process, and effectively inhibit the volume effect caused by the m-phase-t phase transformation, and further improve the sintering strength of the ceramic filter.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0007] A method for preparing a ceramic filter for high-temperature alloy precision casting comprises the following steps: preparing a ceramic premixed liquid, pretreating a precursor, slurry treatment, and calcining and forming.
[0008] The method for preparing the ceramic premix is to mix and disperse ceramic powder, nano zirconium oxide sol, binder, defoamer, surface wetting agent and thickener uniformly through ball milling to obtain a premix with a specific gravity of 3.05-3.25 g / cm 3 Ceramic premix;
[0009] The ceramic powders are: 50-100 mesh zirconium oxide powder, 100-200 mesh zirconium oxide powder, 325 mesh zirconium oxide powder, 1000 mesh zirconium oxide powder, and magnesium oxide.
[0010] In the ceramic premix, the zirconium content of the nano zirconium oxide sol is 10-12wt%;
[0011] The binder includes polyvinyl alcohol PVA solution and polyethylene glycol 6000; the weight ratio of the polyvinyl alcohol PVA solution to the polyethylene glycol 6000 is 14-15:1; the concentration of the polyvinyl alcohol PVA solution is 4.5-5wt%;
[0012] The defoamer is at least one of the following: an organosilicon defoamer, a polyether defoamer, or a polyether-modified silicon defoamer;
[0013] The surface wetting agent is polyethylene glycol 400;
[0014] The thickener is at least one of the following: sodium lignosulfonate, xanthan gum, and starch.
[0015] In the preparation of the ceramic premix, the amount of each raw material is as follows, by weight: 18-25 parts of 50-100 mesh zirconium oxide powder, 15-25 parts of 100-200 mesh zirconium oxide powder, 12-18 parts of 325 mesh zirconium oxide powder, 25-32 parts of 1000 mesh zirconium oxide powder, 4-6 parts of magnesium oxide, 5-10 parts of nano zirconium sol, 14-16 parts of binder, 0.05-0.1 parts of defoamer, 0.1-0.15 parts of surface wetting agent, and 0.8-1.2 parts of thickener.
[0016] The method for pretreating the precursor is as follows: using a high-pressure air gun to blow off the residue on the surface of the polyurethane sponge precursor, transferring it into an alcohol tank, completely immersing it in the alcohol for 3-5 hours, and then taking it out for drying; then evenly coating the polyurethane sponge precursor with electrostatic flocking glue, controlling the coating thickness of the electrostatic flocking glue on the outer surface of the polyurethane sponge precursor to be 0.1-0.15mm, and then transferring it between the plates of the electrostatic flocking device to perform electrostatic flocking treatment, after electrostatically flocking the modified carbon fiber on the outer surface of the polyurethane sponge precursor, transferring it into an oven for drying at 100-120°C to obtain a pretreated precursor.
[0017] In the precursor pretreatment, the preparation method of the modified carbon fiber is to put the carbon fiber with a length of 1-1.5 mm into a nitric acid solution of 3-4 times the weight, immerse for 5-7 hours, filter out and transfer to a calcining furnace, heat to 400-420° C. in an air atmosphere environment, and calcine for 60-90 minutes to obtain the modified carbon fiber;
[0018] The concentration of the nitric acid solution is 1-1.2 mol / L.
[0019] During the electrostatic flocking treatment, the electrostatic voltage is controlled to be 40-42KV, the distance between the plates in the electrostatic flocking device is 7-8cm, the electrostatic flocking time is 9-10s, and the electrostatic flocking density of the modified carbon fiber is 0.25-0.3g / cm 3 .
[0020] The pore density of the polyurethane sponge precursor is 10-40 PPI.
[0021] The method of slurry treatment is to completely immerse the pretreated precursor into the ceramic premixed liquid for slurry treatment, and to control the degree of extrusion by adjusting the gap between the extrusion rollers of the regulator to control the bulk density of the precursor after slurry immersion to 0.65-0.75 g / cm 3 , and then placed in a drying oven with mesh, dried at 60-80℃ for 12-24h to obtain a slurry precursor; then the ceramic spray liquid is sprayed onto the outer surface of the slurry precursor, and the bulk density of the precursor after spraying is controlled to be 0.75-0.9g / cm 3 , and then placed in an oven and dried at 100-120°C for 12 hours or more to obtain a slurry precursor.
[0022] In the slurry treatment, the ceramic spraying liquid is a mixture of ceramic premixed liquid and water, and the specific gravity of the ceramic spraying liquid is 2.75-2.85g / cm 3 .
[0023] The calcination molding method comprises the following steps: evenly spreading 50-80 mesh zircon sand on the surface of a support plate of an electric furnace, placing a slurry precursor on the support plate of the electric furnace, controlling the heating rate to be 60-65°C / h, heating to 600-900°C, and calcining for 2-5 hours, then controlling the heating rate to be 200-210°C / h, heating to 1620-1650°C, calcining for 3-5 hours, and then cooling naturally to obtain a ceramic filter for precision casting of high-temperature alloys.
[0024] A ceramic filter for high-temperature alloy precision casting is prepared by the above-mentioned preparation method.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) The preparation method of the ceramic filter for high-temperature alloy precision casting of the present invention, in the step of preparing the ceramic premix, the ceramic powder adopts 50-100 mesh zirconium oxide powder, 100-200 mesh zirconium oxide powder, 325 mesh zirconium oxide powder, 1000 mesh zirconium oxide powder, magnesium oxide particle grading, and at the same time, the in-situ compensation ceramic additive nano zirconium oxide sol is used to maintain the wetting performance and fluidity of the ceramic premix, enhance the solid content of the precursor, improve its sintering strength, and control the crystal phase of the precursor during the sintering process The modified carbon fiber is flocked to the outer surface of the polyurethane sponge precursor by electrostatic flocking to obtain a pretreated precursor. The hydrophilicity of the surface of the precursor is further improved by the hydrophilic effect of the modified carbon fiber, thereby improving the slurry effect in the subsequent slurry treatment process. Then, in the slurry treatment step, the precursor is treated by slurry treatment and ceramic spray liquid to control the bulk density of the precursor to 0.75-0.9 g / cm 3 , there is no need for multiple slurry treatments, which improves production efficiency and effectively avoids the problems of thin connecting ribs and low skeleton strength caused by poor slurry in the preparation of existing ceramic filters, improves the strength performance of ceramic filters, and avoids the problem of slag falling during the use of ceramic filters; finally, after calcination and molding, a ceramic filter for high-temperature alloy precision casting is obtained, which further improves the strength and thermal shock resistance of the ceramic filter; the aforementioned technical means cooperate and work synergistically with each other to effectively avoid the problems of hole blockage and slag falling in the high-temperature precision casting process of ceramic filters; effectively improve the slurry performance of ceramic filters in the preparation process, effectively inhibit the volume effect caused by the m-phase-t phase transformation, and further improve the sintering strength of ceramic filters.
[0027] (2) The preparation method of the ceramic filter for high-temperature alloy precision casting of the present invention has no sintering deformation or cracking after calcination and the porosity of the ceramic filter is 85.0-85.3%, the compressive strength at room temperature is 3.1-3.2 MPa, and the volume density is 0.87-0.90 g / cm 3 The flexural strength at 1400℃ is 0.62-0.65MPa, and the fire-resistant temperature can reach 1820℃.
[0028] (3) The ceramic filter for high-temperature alloy precision casting of the present invention is heated from room temperature to 1100°C at a heating rate of 20°C / min, kept at this temperature for 2 hours, and then cooled to room temperature at a cooling rate of 20°C / min. After four consecutive rapid heating and cooling processes, no cracks occur in the ceramic filter, and no three or more consecutive connecting ribs of the ceramic filter are broken. The room-temperature compressive strength of the ceramic filter can still reach 2.8-2.9MPa.
[0029] (4) The method for preparing the ceramic filter for high-temperature alloy precision casting of the present invention has easy-to-obtain raw materials, a simple process flow, and easy-to-control process, which is conducive to large-scale industrial production. DETAILED DESCRIPTION
[0030] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.
[0031] Example 1
[0032] This embodiment provides a method for preparing a ceramic filter for high-temperature alloy precision casting, specifically:
[0033] 1. Preparation of ceramic premix
[0034] The ceramic powder, nano zirconium oxide sol, binder, defoamer, surface wetting agent and thickener were uniformly dispersed by ball milling to obtain a specific gravity of 3.05 g / cm 3 Ceramic premix.
[0035] Wherein, the ceramic powder is: 50-100 mesh zirconium oxide powder, 100-200 mesh zirconium oxide powder, 325 mesh zirconium oxide powder, 1000 mesh zirconium oxide powder, and magnesium oxide.
[0036] The zirconium content of the nano zirconium oxide sol is 10wt%.
[0037] The binder includes polyvinyl alcohol PVA solution and polyethylene glycol 6000, wherein the weight ratio of the polyvinyl alcohol PVA solution to the polyethylene glycol 6000 is 14:1. The concentration of the polyvinyl alcohol PVA solution is 4.5wt%, and the model of the polyvinyl alcohol PVA is BP-05A.
[0038] The defoaming agent is a silicone defoaming agent.
[0039] The surface wetting agent is polyethylene glycol 400.
[0040] The thickener is sodium lignosulfonate.
[0041] In parts by weight, the amounts of the above-mentioned raw materials are: 18 parts of 50-100 mesh zirconium oxide powder, 15 parts of 100-200 mesh zirconium oxide powder, 12 parts of 325 mesh zirconium oxide powder, 25 parts of 1000 mesh zirconium oxide powder, 4 parts of magnesium oxide, 5 parts of nano zirconium sol, 14 parts of binder, 0.05 parts of defoamer, 0.1 parts of surface wetting agent, and 0.8 parts of thickener.
[0042] 2. Precursor pretreatment
[0043] A high-pressure air gun was used to blow off the residue on the surface of the polyurethane sponge precursor, and the precursor was transferred into an alcohol tank and completely immersed in the alcohol for 3 hours, then taken out and dried; then the electrostatic flocking glue was evenly coated on the polyurethane sponge precursor, and the coating thickness of the electrostatic flocking glue on the outer surface of the polyurethane sponge precursor was controlled to be 0.1 mm, and then the precursor was transferred between the plates of the electrostatic flocking device for electrostatic flocking treatment. After the modified carbon fiber was electrostatically flocked on the outer surface of the polyurethane sponge precursor, the precursor was transferred into an oven and dried at 100 °C to obtain a pretreated precursor.
[0044] Among them, the preparation method of modified carbon fiber is as follows: put carbon fiber with a length of 1 mm into 3 times the weight of nitric acid solution (concentration 1 mol / L), immerse it for 5 hours, filter it out and transfer it into a calcination furnace, heat it to 400°C in an air atmosphere, and calcine it for 60 minutes to obtain modified carbon fiber.
[0045] During the electrostatic flocking process, the electrostatic voltage was controlled to be 40KV, the distance between the electrodes in the electrostatic flocking device was 7cm, the electrostatic flocking time was 9s, and the electrostatic flocking density of the modified carbon fiber was 0.25g / cm 3 .
[0046] The polyurethane sponge precursor used in this embodiment is purchased from a commercial source. The manufacturer is Anke Plastic (Shanghai) Co., Ltd., and the pore density is 20 PPI.
[0047] 3. Slurry treatment
[0048] The pre-treated precursor is completely immersed in the ceramic premixed liquid for slurry treatment, and the extrusion degree is controlled by adjusting the gap between the extrusion rollers of the regulator to control the bulk density of the precursor after slurry immersion to 0.65g / cm 3 , and then placed in a drying oven with mesh, dried at 70 ° C for 24 hours to obtain a slurry precursor; then the ceramic spray liquid was sprayed onto the outer surface of the slurry precursor, and the bulk density of the precursor after spraying was controlled to be 0.75g / cm 3 , and then placed in an oven and dried at 100°C for 12 hours to obtain a slurry precursor.
[0049] The ceramic spraying liquid is a mixture of ceramic premixed liquid and water, and the specific gravity of the ceramic spraying liquid is 2.75g / cm 3 .
[0050] 4. Calcination and molding
[0051] Spread 50-80 mesh zircon sand evenly on the surface of the support plate of the electric furnace, then place the slurry precursor on the support plate of the electric furnace, control the heating rate to 60℃ / h, heat it to 600℃, keep it warm and calcine for 5h, then control the heating rate to 200℃ / h, heat it to 1620℃, keep it warm and calcine for 3h, and then cool it down naturally to obtain a ceramic filter for high-temperature alloy precision casting.
[0052] This embodiment also provides a ceramic filter for high-temperature alloy precision casting produced by the aforementioned method.
[0053] Example 2
[0054] This embodiment provides a method for preparing a ceramic filter for high-temperature alloy precision casting, specifically:
[0055] 1. Preparation of ceramic premix
[0056] Ceramic powder, nano zirconium oxide sol, binder, defoamer, surface wetting agent and thickener were uniformly dispersed by ball milling to obtain a specific gravity of 3.15 g / cm 3 Ceramic premix.
[0057] Wherein, the ceramic powder is: 50-100 mesh zirconium oxide powder, 100-200 mesh zirconium oxide powder, 325 mesh zirconium oxide powder, 1000 mesh zirconium oxide powder, and magnesium oxide.
[0058] The zirconium content of the nano-zirconia sol is 11wt%.
[0059] The binder includes polyvinyl alcohol PVA solution and polyethylene glycol 6000, wherein the weight ratio of the polyvinyl alcohol PVA solution to the polyethylene glycol 6000 is 14:1. The concentration of the polyvinyl alcohol PVA solution is 4.8wt%, and the model of the polyvinyl alcohol PVA is BP-05A.
[0060] The defoaming agent is a polyether defoaming agent.
[0061] The surface wetting agent is polyethylene glycol 400.
[0062] The thickeners are sodium wood sulfonate and xanthan gum; the weight ratio of sodium wood sulfonate to xanthan gum is 3:1.
[0063] In parts by weight, the amounts of the above-mentioned raw materials are: 21 parts of 50-100 mesh zirconium oxide powder, 20 parts of 100-200 mesh zirconium oxide powder, 16 parts of 325 mesh zirconium oxide powder, 29 parts of 1000 mesh zirconium oxide powder, 5 parts of magnesium oxide, 8 parts of nano zirconium sol, 15 parts of binder, 0.08 parts of defoamer, 0.12 parts of surface wetting agent, and 1 part of thickener.
[0064] 2. Precursor pretreatment
[0065] A high-pressure air gun was used to blow off the residue on the surface of the polyurethane sponge precursor, and the precursor was transferred into an alcohol tank and completely immersed in the alcohol for 4 hours, then taken out and dried; then the electrostatic flocking glue was evenly coated on the polyurethane sponge precursor, and the coating thickness of the electrostatic flocking glue on the outer surface of the polyurethane sponge precursor was controlled to be 0.12 mm, and then the precursor was transferred between the plates of the electrostatic flocking device for electrostatic flocking treatment. After the modified carbon fiber was electrostatically flocked on the outer surface of the polyurethane sponge precursor, the precursor was transferred into an oven and dried at 110 °C to obtain a pretreated precursor.
[0066] Among them, the preparation method of modified carbon fiber is as follows: put carbon fiber with a length of 1.2 mm into 3.5 times the weight of nitric acid solution (concentration 1.1 mol / L), immerse for 6 hours, filter out and transfer into a calcination furnace, heat to 410°C in an air atmosphere, and calcine for 80 minutes to obtain modified carbon fiber.
[0067] During the electrostatic flocking process, the electrostatic voltage was controlled to be 41KV, the distance between the electrodes in the electrostatic flocking device was 7.5cm, the electrostatic flocking time was 9.5s, and the electrostatic flocking density of the modified carbon fiber was 0.28g / cm 3 .
[0068] The polyurethane sponge precursor used in this embodiment is purchased from a commercial source. The manufacturer is Anke Plastic (Shanghai) Co., Ltd., and the pore density is 20 PPI.
[0069] 3. Slurry treatment
[0070] The pre-treated precursor is completely immersed in the ceramic premixed liquid for slurry treatment, and the extrusion degree is controlled by adjusting the gap between the extrusion rollers of the regulator to control the bulk density of the precursor after slurry immersion to 0.7g / cm 3 , and then placed in a drying oven with mesh, dried at 75 ° C for 22 hours to obtain a slurry precursor; then the ceramic spray liquid was sprayed onto the outer surface of the slurry precursor, and the bulk density of the precursor after spraying was controlled to be 0.8g / cm 3 , and then placed in an oven and dried at 110°C for 12 hours to obtain a slurry precursor.
[0071] The ceramic spraying liquid is a mixture of ceramic premixed liquid and water, and the specific gravity of the ceramic spraying liquid is 2.8g / cm 3 .
[0072] 4. Calcination and molding
[0073] Spread 50-80 mesh zircon sand evenly on the surface of the support plate of the electric furnace, then place the slurry precursor on the support plate of the electric furnace, control the heating rate to 62℃ / h, heat it to 800℃, keep it warm and calcine it for 3h, then control the heating rate to 205℃ / h, heat it to 1640℃, keep it warm and calcine it for 4h, and then cool it down naturally to obtain a ceramic filter for high-temperature alloy precision casting.
[0074] This embodiment also provides a ceramic filter for high-temperature alloy precision casting produced by the aforementioned method.
[0075] Example 3
[0076] This embodiment provides a method for preparing a ceramic filter for high-temperature alloy precision casting, specifically:
[0077] 1. Preparation of ceramic premix
[0078] The ceramic powder, nano zirconium oxide sol, binder, defoamer, surface wetting agent and thickener were uniformly dispersed by ball milling to obtain a specific gravity of 3.25 g / cm 3 Ceramic premix.
[0079] Wherein, the ceramic powder is: 50-100 mesh zirconium oxide powder, 100-200 mesh zirconium oxide powder, 325 mesh zirconium oxide powder, 1000 mesh zirconium oxide powder, and magnesium oxide.
[0080] The zirconium content of the nano zirconium oxide sol is 12wt%.
[0081] The binder includes polyvinyl alcohol PVA solution and polyethylene glycol 6000, wherein the weight ratio of the polyvinyl alcohol PVA solution to the polyethylene glycol 6000 is 15:1. The concentration of the polyvinyl alcohol PVA solution is 5wt%, and the model of the polyvinyl alcohol PVA is BP-05A.
[0082] The defoamer is a polyether modified silicone defoamer.
[0083] The surface wetting agent is polyethylene glycol 400.
[0084] The thickener is starch.
[0085] In parts by weight, the amounts of the above-mentioned raw materials are: 25 parts of 50-100 mesh zirconium oxide powder, 25 parts of 100-200 mesh zirconium oxide powder, 18 parts of 325 mesh zirconium oxide powder, 32 parts of 1000 mesh zirconium oxide powder, 6 parts of magnesium oxide, 10 parts of nano zirconium sol, 16 parts of binder, 0.1 parts of defoamer, 0.15 parts of surface wetting agent, and 1.2 parts of thickener.
[0086] 2. Precursor pretreatment
[0087] A high-pressure air gun was used to blow off the residue on the surface of the polyurethane sponge precursor, and the precursor was transferred into an alcohol tank and completely immersed in the alcohol for 5 hours, then taken out and dried; then the electrostatic flocking glue was evenly coated on the polyurethane sponge precursor, and the coating thickness of the electrostatic flocking glue on the outer surface of the polyurethane sponge precursor was controlled to be 0.15 mm, and then the precursor was transferred between the plates of the electrostatic flocking device for electrostatic flocking treatment. After the modified carbon fiber was electrostatically flocked on the outer surface of the polyurethane sponge precursor, the precursor was transferred into an oven and dried at 120 ℃ to obtain a pretreated precursor.
[0088] Among them, the preparation method of modified carbon fiber is as follows: put carbon fiber with a length of 1.5 mm into 4 times the weight of nitric acid solution (concentration 1.2 mol / L), immerse for 7 hours, filter out and transfer into a calcination furnace, heat to 420°C in an air atmosphere, and calcine for 90 minutes to obtain modified carbon fiber.
[0089] During the electrostatic flocking process, the electrostatic voltage was controlled to be 42KV, the distance between the electrodes in the electrostatic flocking device was 8cm, the electrostatic flocking time was 10s, and the electrostatic flocking density of the modified carbon fiber was 0.3g / cm 3 .
[0090] The polyurethane sponge precursor used in this embodiment is purchased from a commercial source. The manufacturer is Anke Plastic (Shanghai) Co., Ltd., and the pore density is 20 PPI.
[0091] 3. Slurry treatment
[0092] The pre-treated precursor is completely immersed in the ceramic premixed liquid for slurry treatment, and the extrusion degree is controlled by adjusting the gap between the extrusion rollers of the regulator to control the bulk density of the precursor after slurry immersion to 0.75g / cm 3 , and then placed in a drying oven with mesh, dried at 80 ° C for 20 hours to obtain a slurry precursor; then the ceramic spray liquid was sprayed onto the outer surface of the slurry precursor, and the bulk density of the precursor after spraying was controlled to be 0.9g / cm 3 , and then placed in an oven and dried at 120°C for 12 hours to obtain a slurry precursor.
[0093] The ceramic spraying liquid is a mixture of ceramic premixed liquid and water, and the specific gravity of the ceramic spraying liquid is 2.85g / cm 3 .
[0094] 4. Calcination and molding
[0095] Spread 50-80 mesh zircon sand evenly on the surface of the support plate of the electric furnace, then place the slurry precursor on the support plate of the electric furnace, control the heating rate to 65℃ / h, heat it to 900℃, keep it warm and calcine it for 2h, then control the heating rate to 210℃ / h, heat it to 1650℃, keep it warm and calcine it for 5h, and then cool it down naturally to obtain a ceramic filter for high-temperature alloy precision casting.
[0096] This embodiment also provides a ceramic filter for high-temperature alloy precision casting produced by the aforementioned method.
[0097] Comparative Example 1
[0098] Comparative Example 1 adopts the technical solution of Example 1, except that in the precursor pretreatment step, the electrostatic flocking treatment is omitted, and the polyurethane sponge precursor after alcohol immersion and cleaning is used as a pretreatment precursor for subsequent treatment.
[0099] Comparative Example 2
[0100] Comparative Example 2 adopts the technical solution of Example 1, except that: 1) the addition of nano zirconium oxide sol is omitted; 2) in the ceramic powder, 50-100 mesh zirconium oxide powder, 100-200 mesh zirconium oxide powder, and 1000 mesh zirconium oxide powder are omitted, and 325 mesh zirconium oxide powder is used to make up the weight.
[0101] Observe whether the ceramic filters after calcination and forming in Examples 1-3 and Comparative Examples 1-2 have sintering deformation and cracking; test the porosity, room temperature compressive strength, bulk density, 1400°C flexural strength, refractory temperature, and 1100°C thermal shock resistance of the ceramic filters of Examples 1-3 and Comparative Examples 1-2.
[0102] Among them, the detection method of 1100℃ thermal shock resistance is to heat the ceramic filter from room temperature to 1100℃ at a heating rate of 20℃ / min, keep it warm for 2h, and then cool it to room temperature at a cooling rate of 20℃ / min. After performing the aforementioned rapid heating and rapid cooling process (thermal shock cycle) for 4 consecutive times, observe whether cracks appear in the ceramic filter, and at the same time observe whether there are 3 or more consecutive connecting ribs broken in the ceramic filter; and test the room-temperature compressive strength of the ceramic filter after 4 consecutive thermal shock cycles.
[0103] The specific results are shown in the following table:
[0104]
[0105] It can be seen that in the preparation method of the ceramic filter for high-temperature alloy precision casting of the present invention, in the step of preparing the ceramic premix, the ceramic powder adopts 50-100 mesh zirconium oxide powder, 100-200 mesh zirconium oxide powder, 325 mesh zirconium oxide powder, 1000 mesh zirconium oxide powder, and magnesium oxide particle grading, and at the same time, the in-situ compensation ceramic additive nano zirconium oxide sol is used, while maintaining the wetting performance and fluidity of the ceramic premix, enhancing the solid content of the precursor, improving its sintering strength, and controlling the crystallization of the precursor during the sintering process. Phase transformation is performed to form magnesium-stabilized zirconia powder, which effectively inhibits the volume effect caused by the m-phase-t phase transformation; in the precursor pretreatment step, electrostatic flocking is used to flock the modified carbon fiber to the outer surface of the polyurethane sponge precursor to obtain a pretreated precursor, and the hydrophilicity of the precursor surface is further improved through the hydrophilic effect of the modified carbon fiber, thereby improving the slurry effect in the subsequent slurry treatment process; then in the slurry treatment step, the precursor is treated with a slurry treatment in combination with a ceramic spray liquid to control the bulk density of the precursor to 0.75-0.9g / cm 3 , there is no need for multiple slurry treatments, which improves production efficiency and effectively avoids the problems of thin connecting ribs and low skeleton strength caused by poor slurry in the preparation of existing ceramic filters, improves the strength performance of ceramic filters, and avoids the problem of slag falling during the use of ceramic filters; finally, after calcination and molding, a ceramic filter for high-temperature alloy precision casting is obtained, which further improves the strength and thermal shock resistance of the ceramic filter; the aforementioned technical means cooperate and work synergistically with each other to effectively avoid the problems of hole blockage and slag falling in the high-temperature precision casting process of ceramic filters; effectively improve the slurry performance of ceramic filters in the preparation process, effectively inhibit the volume effect caused by the m-phase-t phase transformation, and further improve the sintering strength of ceramic filters.
[0106] Unless otherwise specified, all percentages used in the present invention are by mass.
[0107] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a ceramic filter for high-temperature alloy precision casting, characterized in that: The method comprises the following steps: preparing ceramic premixed liquid, pretreating precursor, slurry treatment, and calcining and forming; The method for preparing the ceramic premix is to uniformly grind ceramic powder, nano zirconium oxide sol, binder, defoamer, surface wetting agent and thickener to obtain a premix with a specific gravity of 3.05-3.25 g / cm 3 Ceramic premix; The ceramic powder is composed of the following raw materials: 50-100 mesh zirconium oxide powder, 100-200 mesh zirconium oxide powder, 325 mesh zirconium oxide powder, 1000 mesh zirconium oxide powder, and magnesium oxide; In the preparation of the ceramic premix, the amount of each raw material is as follows by weight: 18-25 parts of 50-100 mesh zirconium oxide powder, 15-25 parts of 100-200 mesh zirconium oxide powder, 12-18 parts of 325 mesh zirconium oxide powder, 25-32 parts of 1000 mesh zirconium oxide powder, 4-6 parts of magnesium oxide, 5-10 parts of nano zirconium oxide sol, 14-16 parts of binder, 0.05-0.1 parts of defoamer, 0.1-0.15 parts of surface wetting agent, and 0.8-1.2 parts of thickener; The precursor pretreatment method comprises the following steps: applying electrostatic flocking glue to the outer surface of the cleaned polyurethane sponge precursor, controlling the coating thickness of the electrostatic flocking glue on the outer surface of the polyurethane sponge precursor to be 0.1-0.15 mm; and then transferring the electrostatic flocking glue to the electrodes of the electrostatic flocking device, controlling the electrostatic voltage to be 40-42 KV, the electrode spacing in the electrostatic flocking device to be 7-8 cm, the electrostatic flocking time to be 9-10 s, and the electrostatic flocking density of the modified carbon fiber to be 0.25-0.3 g / cm 3 , performing electrostatic flocking treatment, electrostatically flocking the modified carbon fiber onto the outer surface of the polyurethane sponge precursor, and drying to obtain a pre-treated precursor; The pore density of the polyurethane sponge precursor is 10-40 PPI; The modified carbon fiber preparation method comprises the following steps: putting carbon fiber with a length of 1-1.5 mm into a nitric acid solution with a concentration of 1-1.2 mol / L, filtering out the carbon fiber after immersion, transferring the carbon fiber into a calcining furnace, heating the carbon fiber to 400-420° C. in an air atmosphere, and calcining the carbon fiber at the temperature to obtain the modified carbon fiber; The method of slurry treatment is to completely immerse the pretreated precursor into the ceramic premixed liquid, and control the bulk density of the precursor after slurry immersion to be 0.65-0.75g / cm 3 , drying to obtain a slurry precursor; then spraying the ceramic spray liquid onto the outer surface of the slurry precursor, controlling the bulk density of the precursor after spraying to be 0.75-0.9g / cm 3 , drying to obtain a slurry precursor; The ceramic spraying liquid is a mixture of ceramic premixed liquid and water; The slurry precursor is calcined and formed to obtain a ceramic filter for high-temperature alloy precision casting.
2. The method for preparing a ceramic filter for high temperature alloy precision casting according to claim 1, characterized in that: The zirconium content of the nano zirconium oxide sol is 10-12wt%; The binder is polyvinyl alcohol solution and polyethylene glycol 6000; The surface wetting agent is polyethylene glycol 400.
3. The method for preparing a ceramic filter for high temperature alloy precision casting according to claim 2, characterized in that: In the binder, the weight ratio of polyvinyl alcohol solution to polyethylene glycol 6000 is 14-15:1; The concentration of the polyvinyl alcohol solution is 4.5-5wt%.
4. The method for preparing a ceramic filter for high temperature alloy precision casting according to claim 1, characterized in that: In the slurry treatment, the specific gravity of the ceramic spraying liquid is 2.75-2.85 g / cm 3 .
5. The method for preparing a ceramic filter for high temperature alloy precision casting according to claim 1, characterized in that: The calcination molding method is as follows: placing the slurry precursor on the support plate of the electric furnace, controlling the heating rate to be 60-65°C / h, heating to 600-900°C, keeping the temperature for calcination, then controlling the heating rate to be 200-210°C / h, heating to 1620-1650°C, keeping the temperature for calcination, and naturally cooling the temperature to obtain a ceramic filter for high-temperature alloy precision casting.
6. A ceramic filter for high temperature alloy precision casting, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 5.
Citation Information
Patent Citations
Ceramic foam and process for forming same
CN1037498A
Zirconia porous body and its manufacturing method
JP2006124256A
Cited By
Silicon carbide ceramic filter with bionic structure design and 3D printing method thereof
CN121850718A